TIME ANALYSIS OF VIRTUAL SPECTRUM ANALYZER - Winiecki, Wieslaw; Bilski, Piotr (International Journal of Computing, 2014)
The problem of the Real-Time virtual instrument is presented. The requirements for the Real-Time conditions are explained. The method of the instrument time analysis is proposed. The virtual spectrum analyser is examined in order to reveal properties of the software functions. The optimisation procedure is described and its results are presented. The conclusions for the future developers have been articulated.